Hubungan Durasi Penggunaan Handphone Dengan Kecerdasan Emosional Pada Anak Kelas 4-6 di SD N 2 Kedungwringin - Susan Venasari; Maya Safitri; Noor Yunida Triana (Pusat riset dan Inovasi Nasional, 2025)
Excessive use of mobile phones can impact children's emotional intelligence development. This study aims to analyze the relationship between the duration of mobile phone use and emotional intelligence among students in grades 4–6 at SD Negeri 2 Kedungwringin. This research employed a quantitative approach with a cross-sectional design. The sample consisted of 43 students selected using accidental sampling. Data were collected through a questionnaire that had been tested for validity and reliability. Data analysis was conducted using the Spearman Rank test. The results showed that the majority of students used mobile phones for a short duration (<2 hours) at 58.1%, moderate duration (2–3 hours) at 27.9%, and excessive duration (>3 hours) at 14.0%. Statistical analysis revealed a significant negative correlation between the duration of mobile phone use and children’s emotional intelligence, with a p-value of 0.010 (<0.05) and a correlation coefficient of -0.387. This indicates that the shorter the duration of mobile phone use, the better the child's emotional intelligence. The conclusion of this study is that there is a significant relationship between the duration of mobile phone use and the emotional intelligence of students in grades 4–6. Therefore, it is recommended that parents and teachers supervise and regulate children's mobile phone usage to support healthy and optimal emotional development.